JUMPA Vol.3 No.3 Okt 2016 PENGARUH EFEKTIVITAS PELATIHAN SOFT SKILLS TERHADAP KOMPETENSI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA: PENGARUH EFEKTIVITAS PELATIHAN SOFT SKILLS TERHADAP KOMPETENSI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Hania Aminah Universitas Negeri Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2016)
In order to overcome the problem of unemployment in Indonesia as well as improving the competence of the students, it is the basis for the writer to be able to increase competence, through training. Training is one of to improve a person's competency with the aim to produce optimal performance in line with expectations. The aim of this study was to determine the extent of the influence of soft skills training for the competence of student at Faculty of Economics State University of Jakarta. The study was conducted by using descriptive and explanatory survey. The data collection techniques by observation, interviews, and questionnaires. The results of this study showed that the effectiveness of soft skills training has a positive and significant impact on student competence, where the influence of an impact on a student's self-concept, increase motifs, and knowledge, so that students have the competence to speak in public.